2014
DOI: 10.3390/ph7030265
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Peptides from Fish

Abstract: Antimicrobial peptides (AMPs) are found widely distributed through Nature, and participate in the innate host defense of each species. Fish are a great source of these peptides, as they express all of the major classes of AMPs, including defensins, cathelicidins, hepcidins, histone-derived peptides, and a fish-specific class of the cecropin family, called piscidins. As with other species, the fish peptides exhibit broad-spectrum antimicrobial activity, killing both fish and human pathogens. They are also immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
195
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(200 citation statements)
references
References 226 publications
(399 reference statements)
2
195
0
3
Order By: Relevance
“…The substitution of Ser 12 with Ala significantly impairs the activity of the native peptide, indicating that a polar residue on the hydrophobic face of the peptide is fundamental for activity. This was a key feature also of other AMPs, as previously reported (35,36).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The substitution of Ser 12 with Ala significantly impairs the activity of the native peptide, indicating that a polar residue on the hydrophobic face of the peptide is fundamental for activity. This was a key feature also of other AMPs, as previously reported (35,36).…”
Section: Resultsmentioning
confidence: 99%
“…The mucus layer provides mechanical protective functions, but the prevention of colonization by parasites, bacteria, and fungi is also complemented by the molecules present in the mucus having antimicrobial characteristics. Thus, fish are a good source of AMPs, including defensins, cathelicidins, hepcidins, histone-derived peptides, and piscidins (12,13).…”
mentioning
confidence: 99%
“…Derived from their diversity, fish possess an enormous variety of antimicrobial peptides that provoke a great deal of interest, with many being described (1,2). Among these antimicrobial peptides is hepcidin, a small cysteine-rich molecule discovered at the turn of the twenty-first century, which has been the focus of recent attention.…”
mentioning
confidence: 99%
“…A hepcidin homolog was soon after found in a teleost fish, the hybrid striped bass (Morone saxatilis 3 Morone chrysops) (7), and several others followed (8)(9)(10). However, contrary to mammals, in which a single hepcidin gene exists [with the mouse being the only known exception (11)], the studies performed with other fish species have shown that many teleosts could possess a large number of hepcidin genes (1,12), especially in Perciformes and Pleuronectiformes. This diversity is generally attributed to genome duplications and positive Darwinian selection (13)(14)(15), influenced by host-pathogen interactions, with variations in gene copy number suggested to be lineage-or species-specific.…”
mentioning
confidence: 99%
“…Several AMPs, such as pleurocidin, daxin, misgurin, piscidin, chrysophsin, morocidin, parasin, defensin, hepcidin and dicentracin have been identified in fish, and the results of these investigations have revealed the AMPs' capability to protect fish from infections. Recently, a study on synthetic hepcidin injected in sea bass has confirmed the capability to potentiate the antimicrobial activity against bacteria by administration of AMPs as a new frontier of therapeutic application in farmed fish species [34]. The aim of this study was to evaluate, through the biomolecular approach, the dynamic of expression of a panel of various …”
Section: Discussionmentioning
confidence: 99%